THE IMPACT OF JUST-IN-TIME PRODUCTION SYSTEM OUTCOMES ON COMPETITVE STRAT-EGIES AT JORDANIAN INDUSTRIAL JOINT STOCK COMPANIES - Bani Younes, Areen Jamal Mahmoud; Abu Hussain, Al-Harith Muhammed (Journal of Economic, Administrative and Legal Sciences, 2018)
The present study aimed at showing the effect of the outputs of the production system in a timely manner on competitive strategies in the industrial joint stock companies in Jordan. The study was based on the analytical descriptive approach. The researcher distributed 246 questionnaires to the directors of the administrative departments, their deputies and their assistants, In order to reach the results of this study, 230 responses were analyzed by (93.5%) and 16 (6.5%) were excluded due to their lack of validity for statistical tests. The study concluded several results, the most important of which was the existence of a statistically significant effect at the level of statistical significance of the outputs of the production system at the specified time (reducing production costs, improving product quality, reducing damage rates, achieving competitive advantage, reducing time factor) Cost, differentiation strategy, focus strategy) in the industrial joint stock companies in Jordan. In light of these results, the study recommended a number of recommendations, the most important of which was raising awareness among the departments and leaders of these companies of the concept of outputs of the production system in a timely manner in order to assist in providing creative ideas and ideas that increase the development of the production system and its efficiency and the quality of the products offered.